Integrasi Model Problem Based Learning dengan Nilai-Nilai Islami di Madrasah Ibtidaiyah: Studi Kasus di MIN 2 Medan - Hayati, Arina (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
This research aims to analyze the implementation of Problem Based Learning (PBL) model integrated with Islamic values at Madrasah Ibtidaiyah Negeri (MIN) 2 Medan. This integrated learning approach offers a promising alternative for creating holistic education in Islamic elementary schools. The study employed a descriptive qualitative method with data collection techniques including observation, in-depth interviews, and documentation studies. Research participants consisted of classroom teachers, school principal, and students at MIN 2 Medan. The findings show that the implementation of PBL model integrated with Islamic values successfully enhanced students' critical thinking and problem-solving skills while strengthening their Islamic character. There are four supporting factors for successful implementation: teacher competence, supporting infrastructure, parental support, and conducive school climate, while the challenges include time constraints and balancing the achievement of national curriculum targets with the internalization of Islamic values.